PENGEMBANGAN MODUL MATEMATIKA BERBASIS PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) PADA MATERI KOORDINAT KARTESIUS DI KELAS VIII SMP - Sovia Nada (Jurnal Edukasi dan Penelitian Matematika, 2021)
This study aims to develop a learning materials in the form mathematics module based on Contextual Teaching and Learning (CTL) approach on cartesian coordinat material in the grade VIII SMP. This design uses the Plomp development model consisting of preliminary research, prototyping phase, and assesment phase. The data collection instrument used were interview of sheets, list of ceklis observation of sheets, and questionnaires. Result showed that quality of modul is very valid with construct aspect has characteristics and priciples of the CTL approach, content arranged base on curriculum, language aspect, and graphical aspect. The module also meets  practical criteria based on aspects of easy to used, attractiveness, and time aspects. Keyword – Design research, Module, CTL, cartesian coordinat